2011
DOI: 10.1111/j.1467-9477.2011.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Do We Really Want to Know? The Potentially Negative Effect of Transparency in Decision Making on Perceived Legitimacy

Abstract: Building on the notion of transparency as a strong democratic value and theories of procedural justice, this article reports an explorative experimental test whether transparency in decision making may lead to increased perceived legitimacy in terms of decision acceptance and trust. This is done in a context of difficult decisions of high importance for citizens – namely priority setting in public health care. An experiment was designed in which ordinary citizens were presented with a description of a case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 45 publications
1
58
4
Order By: Relevance
“…14 Procedural legitimacy thus lies at the heart of the transparency and accountability of the decision-making process that warrants democratic representation and effective participation. 15 Such legitimacy is vital to cross-straits negotiations, which inevitably concern issues of constitutionality and sovereignty.…”
Section: Theoretical Conceptsmentioning
confidence: 99%
“…14 Procedural legitimacy thus lies at the heart of the transparency and accountability of the decision-making process that warrants democratic representation and effective participation. 15 Such legitimacy is vital to cross-straits negotiations, which inevitably concern issues of constitutionality and sovereignty.…”
Section: Theoretical Conceptsmentioning
confidence: 99%
“…Greater transparency may also have caused further politicisation because it does not necessarily increase citizens' trust in local government (De Fine Licht, 2011;Grimmelikhuijsen, 2012 Daniels & Sabin, 2008) because it involves the construction of a narrative through which the location decision is justified (Black, 2008, pp. 151-152).…”
Section: Variety Of Argumentationsmentioning
confidence: 99%
“…Way back at 1997, Mechanic, instead advocated a cautious line in which the majority of difficult priority-setting decisions should be made implicit, without public awareness and debate, by ʿmuddling through elegantlyʾ. Some empirical studies, of which one experimental study was performed in Sweden, have shown that increased transparency may actually make people (at least to a point) less trusting than if less or no transparency exists (de Fine Licht, 2011). Hypothetically, it could mean that being aware of the necessity to pit the need for healthcare of some groups against the need for healthcare of other groups (based on severity level or other kinds of criteria), could make the public even more hesitant to accept politicians as decision makers.…”
Section: The Most Important Aspectsmentioning
confidence: 99%
“…In Sweden there are just a handful of studies that address citizens´ view on priority setting and/or rationing in resource allocation situations at the meso level (de Fine Licht, 2011, 2014aFredriksson et al, 2018;Mossialos & King, 1999;Rosén & Karlberg, 2002;Werntoft, Hallberg & Edberg, 2007;Werntoft, Hallberg, Elmståhl & Edberg, 2006;Werntoft, Hallberg, Elmståhl & Edberg, 2005;Wiss, Levin, Andersson & Tinghög, 2017). Three of these studies focused on patient level, but with one or two questions about priority setting at meso level.…”
Section: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation